2005
DOI: 10.1080/07924259.2005.9652185
|View full text |Cite
|
Sign up to set email alerts
|

Dancing to the rhythms of geological time: the biorhythm capabilities of Polychaeta in a geological context

Abstract: Errant polychaete worms in the Orders Eunicida (family Eunicidae) and Phyllodocida (families Nereidae and Polynoidae) exhibit a highly developed biorhythmic capability. The Pacific palolo worms are well known for a precisely timed annual breeding event in which mass spawning occurs at a particular time of day, on one day per year, that day having a fixed relationship to the lunar period. Nereidae and Polynoidae exhibit photoperiodic responses that determine the breeding season by regulation of oocyte growth. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
(56 reference statements)
0
9
0
1
Order By: Relevance
“…At no time did we observe the spontaneous switch between tidal and lunarday activity as described by Olive et al (2005) under the same treatment regime, nor were any phase shifts apparent due to feeding (depicted by the stars in Figure 2a). However, a completely unexpected behavioral activity pattern was observed in one animal (see black trace in Figure 2a), which displayed what is an overt endogenous circadian (24.4 h) pattern of activity.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…At no time did we observe the spontaneous switch between tidal and lunarday activity as described by Olive et al (2005) under the same treatment regime, nor were any phase shifts apparent due to feeding (depicted by the stars in Figure 2a). However, a completely unexpected behavioral activity pattern was observed in one animal (see black trace in Figure 2a), which displayed what is an overt endogenous circadian (24.4 h) pattern of activity.…”
Section: Discussionmentioning
confidence: 78%
“…A pilot study by Olive et al (2005) has indicated that N. virens possesses short-term biological rhythm capabilities. When wild collected worms were maintained in the laboratory under constant light (LL), they displayed outof-burrow feeding phased to a simulated tidal cycle (STC) with a period of 12.4 h (semi-diurnal tidal).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, direct variations in lunar light intensity, from illumination as low as 1.25 × 10 −5 μ E m −2 s −1 (new moon or starlight) to 2.99 × 10 −3 μ E m −2 s −1 (zenith of full moon), are postulated to cause shifts in lunar rhythms in the spawning of marine organisms on a global basis, including echinoids ( Diadema spp. [ Muthiga , 2003; Coppard and Campbell , 2005]), annelids (palolo worms [ Caspers , 1984; Olive et al , 2005]), and fish [ Austin et al , 1975; Gladstone , 2007; Pisingan and Takemura , 2007].…”
Section: Introductionmentioning
confidence: 99%
“…A ordem Eunicida é uma das mais diversificadas dentro dos poliquetas errantes, cujos animais são caracterizados principalmente pela presença de um complexo aparelho bucal endurecido por mineralização ou esclerotização, formado por mandíbulas ventrais e maxilas dorsais (Paxton, 2006) É uma das ordens com registro fóssil mais extenso e melhor estudado, principalmente devido à possibilidade de fossilização do aparelho bucal endurecido dos indivíduos, formando microfósseis chamados de escolecodontes (Olive et al, 2005). Onuphidae é uma das principais famílias dessa ordem, compreendendo anelídeos majoritariamente bentônicos, com maior representatividade nas zonas entremarés, que produzem o tubo onde habitam (Paxton, 1986).…”
Section: Introductionunclassified